PREVALENCE AND CORRELATES OF FRAILTY AMONG COMMUNITY-DWELLING OLDER ADULTS WITH HYPERTENSION. (11th November 2018) - Ma, L; Zhang, Y; Zhang, Y; Zhang, L; Tang, Z
Abstract: Frailty is associated with disability, hospitalization, and mortality. Hypertension is one of the most common chronic diseases in older adults. However, few studies have evaluated the status of frailty and related factors in older adults with hypertension. Thus, we aimed to explore the prevalence and correlates of frailty in old hypertensive patients in China, which has the largest older population in the world. 3844 community-dwelling older adults with hypertension from China Comprehensive Geriatric Assessment Study were included in this study. Frailty was assessed by a well-established frailty index and was defined as a score ≥ 0.25. Hypertension was defined as systolic blood pressure ≥ 140 mm Hg, diastolic blood pressure ≥ 90 mm Hg, current treatment with antihypertensive medication, or a self-reported diagnosis of hypertension. The prevalence rate of frailty in older adults with hypertension was 13.8% in China, the range from the lowest prevalence rate (2.9%) in Eastern China to the highest prevalence rate (16.1%) in Western China. Those participants with both hypertension and frailty had advanced age, higher systolic blood pressure, hemoglobin A1c, creatinine, white blood cells, and lower low-density lipoprotein cholesterol, compared to old robust participants. Those old adults with hypertension who were female, lower education level, rural residence, depressed, had less exercise, worse physical function, more chronic diseases, cognitive impairment, higher waist–hip ratio, and less monthly income, had a higher prevalence of frailty. This study provides the first evidence of the prevalence and correlates of frailty among Chinese community-dwelling older adults with hypertension.